Multiple criteria assessment of apartment building performance for refurbishment purposes - Tupėnaitė, Laura; Kaklauskas, Artūras; Voitov, Igor; Trinkūnas, Vaidotas; Siniak, Nikolai; Gudauskas, Renaldas; Naimavičienė, Jurga; Kanapeckienė, Loreta (International Journal of Strategic Property Management, 2018)
The selection of buildings for refurbishment is a multi-objective problem and it should be based on integrated assessment of the current performance of the buildings. Accurate assessment allows the development of strategies for the optimisation of building performance and the selection of appropriate and most efficient refurbishment measures. This paper presents a computer-based integrated building performance assessment methodology based on the multiple-criteria approach. A case study from the Šiauliai district, Lithuania, illustrates the proposed methodology in use. The assessment results indicate what are the worst performing buildings and help with the selection of appropriate refurbishment measures and estimation of possible outcomes. First Publish Online: 12 Jul 2018